Human Resource Management Practices among Selected Hotels in Mandaue and Cebu Cities: A Phenomenological Study - Artes, Alex B.; Cabatingan, Albim Y.; Delantar, et al., (Future Science / FSH-PH Publications, 2024)
This descriptive or Husserlian phenomenological study explored the lived experiences of the human resource management managers and supervisors among the selected hotels in Mandaue and Cebu cities. It also presented the meaning or the essence of the said lived experiences. These became the feeders for proposals for improvement. Using purposive sampling, ten (10) key informants who are managers in different hotels were selected as the source of information. The findings indicated that the human resources management components in planning, recruitment, maintenance development, and research were practiced with the guidance of HRM objectives. Moreover, some factors facilitated improving HR practices focused on managing human energy and capabilities to improve productivity. Further, there are challenges encountered by the organization that need to be addressed, for if unabated, it will have negative consequences. All the preceding became the basis for the crafting of recommendations for improvement. It was reflected that while the data generally lean toward the positive side, there is still room for further improvement. These opportunities for improvement are the take-off points for management to craft programs to further the practice of human resources management